2010
DOI: 10.1128/mcb.00030-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Reconstitution of γ-Secretase in Drosophila Results in Substrate Specificity

Abstract: The intramembrane aspartyl protease ␥-secretase plays a fundamental role in several signaling pathways involved in cellular differentiation and has been linked with a variety of human diseases, including Alzheimer's disease. Here, we describe a transgenic Drosophila model for in vivo-reconstituted ␥-secretase, based on expression of epitope-tagged versions of the four core ␥-secretase components, Presenilin, Nicastrin, Aph-1, and Pen-2. In agreement with previous cell culture and yeast studies, coexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…6B), indicating that garz is required for ARF79F localization at the Golgi membrane. Consistent with the effect on ARF79F localization, garz function was also required for accumulation of the COPI coat subunit b9-COP in a punctate pattern in epidermal cells (Fig 6E,F) (Stempfle et al, 2010). Although b9-COP distribution was diffuse in garz mutant cells, b9-COP accumulation was rescued by expression of GFP-Garz in stripes of epidermal cells (Fig.…”
Section: The Arf-gef Catalytic Center Is Crucial For Golgi Localizatisupporting
confidence: 78%
See 1 more Smart Citation
“…6B), indicating that garz is required for ARF79F localization at the Golgi membrane. Consistent with the effect on ARF79F localization, garz function was also required for accumulation of the COPI coat subunit b9-COP in a punctate pattern in epidermal cells (Fig 6E,F) (Stempfle et al, 2010). Although b9-COP distribution was diffuse in garz mutant cells, b9-COP accumulation was rescued by expression of GFP-Garz in stripes of epidermal cells (Fig.…”
Section: The Arf-gef Catalytic Center Is Crucial For Golgi Localizatisupporting
confidence: 78%
“…The following antibodies were used: rabbit anti-Serp (1:300) (Luschnig et al, 2006), rabbit anti-Verm (1:300) (Luschnig et al, 2006), guinea pig anti-Verm (1:500) (Wang et al, 2006), rabbit anti-Pio (1:20) (Jazwinska et al, 2003), rabbit anti-b'-COP (1:5000) (Stempfle et al, 2010), rabbit anti-GBF1 (1:1000) (Zhao et al, 2006), rabbit anti-GM130 (1:1000; Abcam), mouse-anti-GFP (1:500; Clontech), rabbit anti-GFP (1:500; gift from Stefan Heidmann, Department of Genetics, University of Bayreuth, Bayreuth, Germany), rabbit anti-mRFP (1:2500; gift from Stefan Heidmann), mouse anti-Golgi p120 (7H6D7C2; 1:250; Calbiochem), mouse anti-KDEL (10C3; 1:10; Abcam), rabbit anti-SAS (1:250; gift from Doug Cavener, Department of Biology, Pennsylvania State University, PA), mouse anti-Fasciclin III (7G10; 1:50; DSHB), rabbit anti-GMAP210 (1:400; Friggi-Grelin et al, 2006), rabbit anti-HA (1:300; Roche). Rhodamine-or FITCconjugated chitin binding probe (1:100; New England Biolabs) was used to detect chitin.…”
Section: Immunofluorescencementioning
confidence: 99%
“…It has been hypothesized that overexpression of Psn forms insoluble complexes that down regulate signaling. Indeed, several studies have highlighted that all four components of the γ-secretase complex have to be expressed for it to be active (Edbauer et al, 2003; Stempfle et al, 2010). Thus, it is likely that an excess of one component of the complex renders it less active.…”
Section: Discussionmentioning
confidence: 99%
“…HBS seems to exert its function by affecting the γ-processing of APPL because it can promote the cleavage of Presenilin (PSN) into its active form (Singh and Mlodzik, 2012). As in vertebrates, the fly γ-secretase consists of NCT, APH1, PEN2, and the catalytically active PSN (Hu and Fortini, 2003;Stempfle et al, 2010) and expression of Drosophila PSN was shown to promote APPL cleavage (Carmine-Simmen et al, 2009). The interaction of HBS with APPL therefore suggests that its function in photoreceptor development and outgrowth requires the C-terminus or more specifically C-terminal cleavage of APPL.…”
Section: Appl and Neuronal Outgrowthmentioning
confidence: 99%
“…Like APP, APPL is processed by several secretases, resulting in secreted fragments, a neurotoxic Aβ-like peptide, and an intracellular AICD (Luo et al, 1990;Carmine-Simmen et al, 2009;Bolkan et al, 2012). However, in comparison to APP, the cleavage sites for the α-and β-secretase are reversed in APPL, with the β-site being more proximal to the transmembrane region and the α-site being more distal (Carmine-Simmen et al, 2009;Stempfle et al, 2010). The evolutionary conservation of APPL and its processing not only suggests that this protein has important physiological functions but also that studies in Drosophila can provide insights into the normal functions of human APP and its proteolytic fragments.…”
mentioning
confidence: 99%